The Direction of the Caller to Producing Investigative Programs in Iraqi Satellite Channels - Ameer Abass, Hussein; Kareem Ahmed, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The investigative programs that have multiple names, are investigative programs or depth programs and researches, etc., which reach the depth of societal phenomena and their issues, and were explained and demonstrated in front of public opinion in the hope of reforming or revealing the hidden and finding treatments, as this study examined a sample consisting of (102) of those in contact in the Iraqi satellite channels, and the study revealed the apparent weakness in the production of survey programs in the Iraqi satellite channels because of the existence of many obstacles that prevent the manufacture of this color of programs, some of these obstacles that are on the governmental and security side and some except T this land factors, self-journalist himself, and that one of the important reasons for the lack of production of this type of programs that represent the satellite channels owned by the ruling parties. The research also concluded that there are some factors,, if available, that would contribute to the development of this programmatic form in Iraqi channels in the future, foremost of which is the provision of a secure journalistic environment and the legislation of laws that provide information and protect journalists from legal prosecutions and threats that affect them due to, as they have shown the study, The lack of institutions concerned with setting up training courses to learn the skills of preparing and producing TV survey programs, and the study reached the volumes of many contractors towards producing survey programs as a result of the lack of interest of the media institutions in these programs and not to encourage public opinion on its production.